Proliferative activity in ovarian endometrrioma - Dubinina, V. G.; Nosenko, O. M.; Gritsenko, G. S. (Journal of Education, Health and Sport, 2018)
Endometriosis shows features similar to neoplasia, which recently increased interest in the monoclonal antigen Ki-67. The aim of the study was to study the expression of Ki-67 in the operated ovarian endometriomas in women of reproductive age. Materials of the study were 32 patients with ovarian endometriomas and 30 patients with tubal infertility in the control group who underwent surgical treatment. Immunohistochemical study was performed by avidin-biotin-peroxidase method according to the standard method. Evaluated the number of positively colored cells using rabbit monoclonal antibodies to Ki-67. In 68.75% of patients with operated endometriomas, active proliferation in ovarian formations is observed, which is manifested by increased expression of oncoprotein Ki-67 in the glandular epithelium, in the cytogenic stroma of the endometrium and in surrounding vessels. There is a direct correlation between the level of Ki-67 expression and the prevalence of the endometriomas.